2018
DOI: 10.3171/2018.9.focus18359
|View full text |Cite
|
Sign up to set email alerts
|

Two-year mortality and functional outcomes in combat-related penetrating brain injury: battlefield through rehabilitation

Abstract: OBJECTIVEThere are limited data concerning the long-term functional outcomes of patients with penetrating brain injury. Reports from civilian cohorts are small because of the high reported mortality rates (as high as 90%). Data from military populations suggest a better prognosis for penetrating brain injury, but previous reports are hampered by analyses that exclude the point of injury. The purpose of this study was to provide a description of the long-term functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 27 publications
1
9
0
1
Order By: Relevance
“…From the military perspective, pTBI was prevalent in recent conflicts in Iraq and Afghanistan and most often results from a blast mechanism. pTBI outcomes in these modern conflicts are better than in past reports, 3–10 most likely because of more aggressive clinical care. 6 Before the conflicts in Iraq and Afghanistan, management in those who survived to reach care included limited surgical debridement and wound closure.…”
Section: Introductionmentioning
confidence: 78%
“…From the military perspective, pTBI was prevalent in recent conflicts in Iraq and Afghanistan and most often results from a blast mechanism. pTBI outcomes in these modern conflicts are better than in past reports, 3–10 most likely because of more aggressive clinical care. 6 Before the conflicts in Iraq and Afghanistan, management in those who survived to reach care included limited surgical debridement and wound closure.…”
Section: Introductionmentioning
confidence: 78%
“…During OIF and OEF, total mortality was approximately 15%-20% lower than in the First Gulf War and, of those patients who survived their initial resuscitation, many achieved a good functional outcome. 16,17 While the long-term functional outcomes of the specific 2003 and 2005 patient cohorts treated by this team are largely unknown due to lack of medical record access or confidentiality, approximately half of patients who survived OIF/OEF had a Glasgow Outcome Scale score greater than 3. 18 In comparison with previous conflicts, like the Vietnam War, where blast injuries were also prominent and forward neurosurgical care available, yet without an intensivist, this metric appears to be maintained despite an escalating incidence of CNS injury and complexity of injury patterns.…”
Section: Neuroteam Evolutionmentioning
confidence: 99%
“…Deep brain stimulation (DBS), in last decades, has been widely used in the routine clinic for the treatment of movement disorders [ 21 26 ], epilepsy [ 27 , 28 ], and obsessive-compulsive disorder [ 29 ], and exploratory studies showed that DBS targeting the thalamus (ventral posterolateral (VPL) nucleus or ventral posteromedial (VPM) nucleus), periventricular grey or periaqueductal grey, or anterior cingulate cortex might have a role in pain control [ 30 , 31 ]. Another invasive technique, which showed promising results, is motor cortex stimulation [ 31 33 ].…”
Section: Neurostimulation Techniques For Chronic Pain Managementmentioning
confidence: 99%